AFFECTS OF LIGHT AND NUTRIENT IN ARTIFICAL SEEDLING PRODUCTION FROM ZYGOTES OF SARGASSUM POLYCYSTUM C. AGARDH - Hậu, Lê Như; Mơ, Vũ Thị; Trung, Võ Thành; Huynh, Trần Văn; Vy, Trần Nguyễn Hà (Vietnam Journal of Marine Science and Technology, 2014)
Increasing the growth of germlings and decreasing fouling algae are two main constraints for the seedling production of Sargassum in laboratory condition. These results indicate that the growth of germlings was best in nutrient concentration of NaNO3 : KH2PO4= 4 : 0,4 mg/L and photon irradiance of 510 µmol photon/m2/s. During the experiment, fouling was controlled by degration of photon irradiance. Seedlings of > 0.2cm length could be achieved after 2 month of tank culture. However, seedlings of 2 cm length could be achieved after 4,5 month of tank culture from seedlings of 0.2 cm length. These results indicate that the growth of seedling was low during their nursery cultivation stage at laboratory. Therefore, successful cultivation in nursery stage is essential for field conduction.